Aerial remote sensing of sub-sea dispersant injection effects during the Deepwater Horizon (MC-252) oil spill. (June 2023) - Svejkovsky, Jan; Hess, Mark; Muskat, Judd; White, James
Abstract: During the Deepwater Horizon oil spill in 2010, subsea dispersant injection (SSDI) was utilized for the first time in an effort to reduce the amount of oil reaching the sea surface and thus potentially decrease its environmental impact and enhance responders' safety. Since then, controversy has developed about SSDI's effectiveness. Most of the analysis is based on modeling, with some models concluding SSDI significantly reduced surfacing oil volumes, and others predicting that processes unrelated to the dispersant caused most of the subsurface oil retention. This study utilized a multispectral aerial sensor image time series to correlate the surface area covered by freshly upwelled oil with changes in SSDI rates, accounting for an approximate 4 hour oil rise time lag. A significant negative correlation was found between oil-covered surface area and SSDI rates, providing direct observation support that the technique did reduce the amount of surfacing oil around the wellhead. Highlights: Multispectral aerial image series allows assessment of surfaced oil above the well head. Negative correlation exists between oil-covered area and subsurface dispersant rates. Correlation results support notion that subsurface dispersant injections were effective.